Welfare Economics and Social Choice Theory - Feldman, Allan M.; Serrano, Roberto; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2006)
Welfare economics, and social choice theory, are disciplines that blend economics, ethics, political science, and mathematics. Topics in Welfare Economics and Social Choice Theory, 2nd Edition, include models of economic exchange and production, uncertainty, optimality, public goods, social improvement criteria, life and death choices, majority voting, Arrow’s theorem, and theories of implementation and mechanism design. Our goal is to make value judgments about economic and political mechanisms: For instance, does the competitive market produce distributions of products and services that are good or bad for society? Does majority voting produce good or bad outcomes? How can we design tax mechanisms that result in efficient amounts of public goods being produced? We have attempted, in this book, to minimize mathematical obstacles, and to make this field accessible to undergraduate and graduate students and the interested non-expert.
Preferences and Utility -- Barter Exchange -- Welfare Properties of Market Exchange -- Welfare Properties of “Jungle” Exchange -- Economies with Production -- Uncertainty in Exchange -- Externalities -- Public Goods -- Compensation Criteria -- Fairness and the Rawls Criterion -- Life and Death Choices -- Majority Voting -- Arrow’s Impossibility Theorem -- Dominant-Strategy Implementation -- Nash Implementation -- Bayesian Implementation -- Epilogue.
Keywords: Economic theory; Microeconomics; Economic Theory/Quantitative Economics/Mathematical Methods; Microeconomics